A Model Of Social Entrepreneurship For Armenia - Voskanyan, Knarik (տպ. Atlas)
This study aims to explore the key barriers to advancing social entrepreneurship and proposes a model for creating innovative solutions to public problems through purposive collaboration between public and private sectors. Using the findings from in-depth interviews with experts and government officials, as well as NGO and business representatives, the research builds upon the available scholarship on the topic, devising a social entrepreneurship model befitting Armenia and similar developing nations. The essence of the model is a design-thinking approach that integrates the role of government in the process of promoting social entrepreneurship; sharing evidence on the critical public problems that need attention; developing targeted tax incentive schemes; promoting entrepreneurial private incentives; rewarding successful initiatives to increase interest and competitiveness; and educating the public to advance social entrepreneurship more broadly.
Keywords: Sociology